Experimental study for rubber pad forming process of AZ31 magnesium alloy sheets at warm temperature. Issue 1 (March 2017) - Xu, Junrui; Zhou, Yingqi; Cui, Junjia; Sun, Guangyong; Li, Gangyao
Abstract In this paper, forming behavior of AZ31 sheet in rubber pad forming with warm temperature was investigated by experimental method. Rubber pad is always considered as it is temperature resistant. However, some types of rubbers can endure warm temperature, such as polyurethane for 120 °C and silica gel for 250 °C. Thus, forming for coupling with effects of temperature and flexible of rubber pad is proposed in this paper. The forming process of AZ31 sheet experienced bulging first and then gradually contacting with die, which was different from conventional forming. Fracture presented flat at room temperature and fracture became dentation obviously at 100 °C. When the temperature elevated to 200 °C, the fracture does not occur but the polyurethane was melted. The AZ31 sheet could fill the die successfully with silica gel as rubber pad at 200 °C. The effects of different load velocity for forming of AZ31 sheet were investigated. Thickness increased at bottom of deformed part, due to pressure stress acted from surrounding area. The thickness deceased at the bottom corner. Microstructure of deformed AZ31 sheet was also analyzed. It was indicated that dynamic recrystallization and twinning deformation mechanics were activated which had positive influence for improving formability of AZ31 sheet.